Proton therapy range verification method via delayed γ-ray spectroscopy of a molybdenum tumour marker. (22nd January 2021) - Burbadge, C; Kasanda, E; Bildstein, V; Dublin, G; Olaizola, B; Höhr, C; Mücher, D
Abstract: In this work, a new method of range verification for proton therapy (PT) is experimentally demonstrated for the first time. If a metal marker is implanted near the tumour site, its response to proton activation will result in the emission of characteristic γ rays. The relative intensity of γ rays originating from competing fusion-evaporation reaction channels provides a unique signature of the average proton energy at the marker, and by extension the beam's range, in vivo and in real time. The clinical feasibility of this method was investigated at the PT facility at TRIUMF with a proof-of-principle experiment which irradiated a naturally-abundant molybdenum foil at various proton beam energies. Delayed characteristic γ rays were measured with two Compton-shielded LaBr3 scintillators. The technique was successfully demonstrated by relating the relative intensity of two γ -ray peaks to the energy of the beam at the Mo target, opening the door to future clinical applications where the range of the beam can be verified in real time.